2014
DOI: 10.1061/(asce)be.1943-5592.0000632
|View full text |Cite
|
Sign up to set email alerts
|

Modal Analysis for the Rehabilitation Assessment of the Luiz I Bridge

Abstract: Dynamic testing in the condition assessment of existing bridges to support their rehabilitation and strengthening designs is becoming a common procedure, yet additional dynamic testing after rehabilitation is rare. Nevertheless, combining the results of dynamic testing before and after bridge rehabilitation produces unique and valuable information regarding changes occurred in a bridge's dynamic properties. Such dual testing would allow researchers to verify the behavior predicted at the design stage and to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The use of natural frequency measurement from accelerometers as a means of measuring the variation in stiffness of steel structures has already been used in numerous works, such as the analysis on steel structure that had changes in its structural stiffness due to renovation processes [ 24 , 25 ]. It has also been used for the calibration of numerical models of actual steel structures and subsequent analysis of their behaviors [ 26 , 27 ], to the monitoring of the static and dynamic displacements of railway bridges with the use of inertial sensors [ 28 ], to measure the earthquake behavior of steel structures in the laboratory [ 29 , 30 ] and has also been used to dynamic assessment of masonry towers based on terrestrial radar interferometer and accelerometers [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural frequency measurement from accelerometers as a means of measuring the variation in stiffness of steel structures has already been used in numerous works, such as the analysis on steel structure that had changes in its structural stiffness due to renovation processes [ 24 , 25 ]. It has also been used for the calibration of numerical models of actual steel structures and subsequent analysis of their behaviors [ 26 , 27 ], to the monitoring of the static and dynamic displacements of railway bridges with the use of inertial sensors [ 28 ], to measure the earthquake behavior of steel structures in the laboratory [ 29 , 30 ] and has also been used to dynamic assessment of masonry towers based on terrestrial radar interferometer and accelerometers [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers [5][6] have been conducted structural assessment and load testing in concrete and steel bridges. Old and historical bridges dominated all cases study that reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several structures are reaching their design life in Europe and America, which leads the engineers to a new concern: the need to develop rehabilitation projects aiming to guarantee structural integrity and design life increase [15]. Rehabilitation is usually an attractive alternative, once it represents between 10% and 30% of the total cost of a similar new structure for most cases [16].…”
Section: Introductionmentioning
confidence: 99%